Studies on Schismatoglottideae (Araceae) of Borneo XXVII – New species of Aridarum, and notes on the Aridarum Rostratum Complex - Boyce, P.C; Wong, Sin Yeng (BioOne Journals Online, 2013)
Two taxonomically novel Aridarum species are described from Kalimantan Barat, Indonesian Borneo: A. hippocrepis P. C. Boyce & S. Y. Wong and A. uncum P. C. Boyce & S. Y. Wong. Together with A. rostratum Bogner & A. Hay (also Kalimantan Barat) these form a morphologically distinct group of unistaminate Aridarum species, here informally dubbed the Aridarum Rostratum Complex, differing from those of the (also unistaminate) Burttii Complex by the inflorescence pendent on an arching to pendent wiry peduncle, by staminate flowers lacking a distally expanded connective, the presence of horseshoe-shaped interstice staminodes that expand laterally post pistillate anthesis and prior to staminate anthesis, by the spathe limb hardly opening at pistillate anthesis and deliquescing acroscopically during staminate anthesis, and by the narrowly campanuliform (not salverform) persistent lower spathe. The Rostratum Complex is further differentiated by leaf blades lacking the adaxially conspicuously raised primary lateral veins that are a characteristic of the Burttii Complex. Recognition of these two new species takes the genus Aridarum to 14 accepted species. An emended species description of A. rostratum is presented and a key to species of the Rostratum Complex is provided. All species are illustrated from living plants, and a comparative plate of the spadices of the three species assigned to the Rostratum Complex is also provided.